If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 + -5x = 31x + 23 Reorder the terms: 83 + -5x = 23 + 31x Solving 83 + -5x = 23 + 31x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-31x' to each side of the equation. 83 + -5x + -31x = 23 + 31x + -31x Combine like terms: -5x + -31x = -36x 83 + -36x = 23 + 31x + -31x Combine like terms: 31x + -31x = 0 83 + -36x = 23 + 0 83 + -36x = 23 Add '-83' to each side of the equation. 83 + -83 + -36x = 23 + -83 Combine like terms: 83 + -83 = 0 0 + -36x = 23 + -83 -36x = 23 + -83 Combine like terms: 23 + -83 = -60 -36x = -60 Divide each side by '-36'. x = 1.666666667 Simplifying x = 1.666666667
| 7x-x^2=11 | | 4x*-15x-4=0 | | 59-2x=16x+21 | | -6(-1)-2= | | -y-6y= | | -x^3+7x^2-11x=0 | | -135-7x=10x | | 12x-34=5x+2 | | 3x-x^2-5=0 | | 5x^8-4x^6-2x^4-4x^2+1=0 | | (n+2)*2=8 | | (n-5)*2=6 | | (n+1)*8=24 | | x^3+2*x^2-19x=0 | | 4-2y+3=-9 | | x^4-3x-4=0 | | 200+3=1800 | | 3*4x-6x=2*9x | | 40t=55+3t | | x-(x-0.2x)=43.46 | | -x^3+5x^2+10x-50=0 | | 12=4x-x | | 2(x-1)=3/5(10+5x) | | 63x^7=7x^5 | | y=-4(2)+5 | | y=-4(1)+5 | | (8x-12)(10-15x)=0 | | y=-4(0)+5 | | y=-4(-1)+5 | | x+2(3)=8 | | 2/3(3x+18)=5x-9 | | 2+3x=5-2 |